Plasma amino acids levels in 1859 physical examination subjects in Hangzhou City in 2020 - He, Xiaojie; Ji, Na; Huang, Xiaoxu; Liu, Meixuan; Wang, Jiali; Sun, Ting (Wei sheng yan jiu, 2022)
To study the relationship between fasting plasma amino acids and obesity in the physical examination population. A total of 1859 persons who underwent physical examination in the Second Affiliated Hospital Zhejiang University School of Medicine from January to December 2020 were enrolled. Fasting plasma amino acids concentrations and body fat ratio(BFR) were respectively determined by ultra-performance liquid chromatography tandem mass spectrometry(UPLC-MS/MS) and Inbody instrument. According to body mass index and gender grouping, Python language was used for data analysis and graphic visualization to explore the relationship between body mass index, gender and plasma amino acids levels. The plasma levels of glycine, serine and asparagine in the overweight and obesity groups were significantly lower than those in the normal group, especially the levels in the obesity group were lower than those in the overweight group in males(P<0.05). There was no significant difference in plasma levels of lysine, tryptopha